Cardiopancreatic Effects of Artocarpus heterophyllus in Mercury Chloride-Exposed Wistar Rats: Biochemical and Histological Evidence - Edobor Obayuwana; Joseph Raymond Enoghase (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Mercury chloride (HgCl2) is a pervasive environmental toxicant that disrupts redox balance and induces structural injury in metabolically active organs, including the heart and pancreas. Artocarpus heterophyllus (jackfruit) contains antioxidant phytochemicals, while vitamin E is an established antioxidant; both may counteract mercury-induced toxicity. This study evaluated the protective effects of aqueous Artocarpus heterophyllus fruit extract and vitamin E on cardiac and pancreatic alterations in HgCl?-exposed Wistar rats. Twenty-five adult Wistar rats (180–200 g) were randomly assigned into five groups (n = 5): control; HgCl? (3 mg/kg); Artocarpus heterophyllus extract (1000 mg/kg); extract + HgCl2 (extract administered 30 min before HgCl2); and vitamin E (200 mg/kg) + HgCl2 (30 min prior). Treatments were given orally once daily for 28 days. Body weights were recorded weekly. At sacrifice, heart and pancreas weights were measured and organ-to-body weight indices calculated. Serum antioxidant markers—superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), and malondialdehyde (MDA)-were assayed. Lipid profile parameters (total cholesterol [TC], triglycerides [TG], HDL-C, and LDL-C) were determined using commercial kits. Cardiac and pancreatic tissues were examined histologically using hematoxylin and eosin staining. Data were analyzed by one-way ANOVA with LSD post-hoc tests (p < 0.05). All animals completed the study. Phytochemical analysis of Artocarpus heterophyllus extract showed high total phenolic (29 ± 0.48) and flavonoid (5.4 ± 1.2) contents, with appreciable levels of saponins (19 ± 1.1), tannins (4.7 ± 0.41), and alkaloids (0.70 ± 0.09). Body weight increased significantly in the control group (p = 0.005), whereas HgCl2-treated rats showed minimal weight change (p = 0.777). Heart and pancreas weights and indices did not differ significantly among groups (p > 0.05). HgCl2 significantly reduced serum SOD and CAT activities compared with control, while GPx activity showed a non-significant downward trend (p = 0.067). Serum MDA was highest in the HgCl2 group, whereas extract- and vitamin E-treated groups showed marked reductions. HgCl2 exposure decreased TC and HDL-C and increased TG (p < 0.001). Histologically, HgCl2 induced interstitial haemorrhage and vascular congestion in the heart and vascular congestion with mild inflammatory infiltrates in the pancreas. These alterations were markedly attenuated by Artocarpus heterophyllus extract and vitamin E, with preservation of normal tissue architecture. Mercury chloride induced oxidative stress, dyslipidaemia, and structural injury in the heart and pancreas. Pre-treatment with phenolic-rich Artocarpus heterophyllus extract or vitamin E ameliorated these effects, supporting the antioxidant and tissue-protective potential of Artocarpus heterophyllus and warranting further mechanistic studies.